Verbum Domini and the Complementarity of Exegesis and Theology - Carl, Scott, 1974- (Book collections on Project MUSE., 2021)
"In Verbum Domini, his 2010 apostolic exhortation, Pope Benedict XVI challenged the church to keep theology firmly rooted in the study of Scripture. The essays collected here respond thoughtfully and concretely to that charge, together demonstrating that exegesis is essential to the theological task and to faith for scholars, students, and the broader Church."--